VD_FINDINFO Pron / 2015 / 31 vom 29. September 2015 - VD Tribunal cantonal (2015)
DÉCISION D'IRRECEVABILITÉ, RETARD INJUSTIFIÉ, FÉRIES JUDICIAIRES | 450b al. 1 CC, 450f CC, 137 CPC, 137 CPC (CH), 12 LVPAE